Analisis Sistem Informasi Akuntansi Pelayanan Pasien Badan Penyelenggara Jaminan Sosial (BPJS) Pada Badan Layanan Umum Daerah (BLUD) Rumah Sakit Umum (RSU) Jampangkulon - Eriansyah, Eri (Jati: Jurnal Akuntansi Terapan Indonesia, 2020)
This study aims to find out how the analysis of accounting information system for BPJS patient service implemented at Jampangkulon Hospital. This research focuses on the BPJS patient importance of this research was carried out because of the many people who use health services in hospital with BPJS Health. Therefore researches are interested in conducting research on the analysis of accounting information system for BPJS patient service. The method used in this research is qualitative method. Data collection techniques used were interviews, observation, and documentation. Data analysis technique used in this study are by: (1) Collecting data to obtain the desired information. (2) Reducing data or summarizing the main points. (3) Present data to obtain conclusions. (4) Summarizing the results of the study. The results showed that the application of accounting informaation system in BPJS patien service at Jampangkulon Hospital has been carried out and the accounting recording system and service procedures used have been affective, because it has fulfilled all elements of the accounting information system, namely human resources, form or documents, work procedures and financial records.